Programas de conformidade e a busca de integridade em organizaç\~oes - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– In the last few years, many Brazilian firms have been strongly interested in programs of compliance as well as in programs of integrity. These matters are also relevant to government offices of inspection and control of public sector activities as well as to offices of regulation of economic affairs in the private sector. The present text is introductory and deals with the importance of programs of integrity. The major reason for them is that they concern in a conscious and more direct way the aim of attaining integrity in a organization. While supporting this assertion, the text distinguishes between programs of risk management, programs of compliance and programs of integrity. Moreover, it explains what is integrity and what role it has.
Keywords: D73; A13; 330; program of integrity; compliance; bureaucratic degeneration; risk management